Meiotic Chromosomal Abnormality Detected in a Heterozygote of Elymus nutans - Liu, Bo; Tao, Xiaoyan; Dou, Quanwen (Frontiers in Plant Science, 2022)
Meiotic analysis was conducted on a heterozygote plant of Elymus nutans, which showed high intra- and inter-genome chromosomal variations, by sequential fluorescence in situ hybridization (FISH) and genome in suit hybridization (GISH), with each chromosome clearly recognized. The results showed chromosomal abnormalities at every meiotic stage and abnormalities in frequency variations between different sub-genomes and different individual chromosomes. The abnormalities were revealed as univalent, fragment, rod, or Y shape bivalent in diakinesis; univalent and rod bivalent in metaphase I; lagged and segregated chromatid, bridge, fragment of the sister chromatid, fragment, bridge accompanied with fragment, and unequal segregated chromosome in anaphase I; bridge and lagged chromatid in ana-telophase Ⅱ; and micronucleus in mononuclear. Generally, the St and H genomes harbor more abnormalities than the Y genome. Moreover, a paracentric inversion in 2St was exclusively determined, and another paracentric inversion in 6Y was tentatively identified. In addition, novel deletions were clearly detected in 3H, 4H, 1Y, and 3Y homologous chromosomes; in particular, de novo pericentric inversion in 3H was repeatedly identified in metaphase I. The reasons for the rise of the primary and secondary chromosomal structural variations and the significance of the genetic diversity and adaptation divergence of E. nutans are further discussed.